Flexible and flex-rigid printed circuit boards basic characterastics for parametric model development - Yevsieiev, V. V.; Miliutina, S.; Salieva, V. E. (ДРУКАРНЯ МАДРИД, 2016)
Flexible and flex-rigid printed circuit boards basic characterastics for parametric model development.